1997
DOI: 10.1093/mnras/289.2.393
|View full text |Cite
|
Sign up to set email alerts
|

ROSAT monitoring of persistent giant and rapid variability in the narrow-line Seyfert 1 galaxy IRAS 13224-3809

Abstract: We report evidence for persistent giant and rapid X-ray variability in the radio-quiet, ultrasoft, strong Fe ii, narrow-line Seyfert 1 galaxy IRAS 13224-3809. Within a 30 day ROSAT High Resolution Imager (HRI) monitoring observation at least five giant amplitude count rate variations are visible, with the maximum observed amplitude of variability being about a factor of 60. We detect a rise by a factor of about 57 in just two days. IRAS 13224-3809 appears to be the most X-ray variable Seyfert known, and its va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 42 publications
5
98
1
Order By: Relevance
“…Therefore if our modeling is correct, either the molecular torus is geometrically thin, optically thin, patchy, or absent altogether or the planes of the AD and the torus are more orthogonal than coincident. Boller et al (1997) suggested that NLS1s in general may contain disks viewed relatively face-on which would contradict the results of our modeling. However, they based this hypothesis on the high levels of variability seen in many NLS1s (and in IRAS 13224È3809 in particular), and RE J1034]396 has shown only relatively small changes over long timescales.…”
Section: Black Hole Mass and Accretion Ratecontrasting
confidence: 90%
See 1 more Smart Citation
“…Therefore if our modeling is correct, either the molecular torus is geometrically thin, optically thin, patchy, or absent altogether or the planes of the AD and the torus are more orthogonal than coincident. Boller et al (1997) suggested that NLS1s in general may contain disks viewed relatively face-on which would contradict the results of our modeling. However, they based this hypothesis on the high levels of variability seen in many NLS1s (and in IRAS 13224È3809 in particular), and RE J1034]396 has shown only relatively small changes over long timescales.…”
Section: Black Hole Mass and Accretion Ratecontrasting
confidence: 90%
“…They have very strong soft X-ray excesses (Puchnarewicz et al 1992 ;Boller, Brandt, & Fink 1996), are often highly variable (Brandt, Fabian, & Pounds 1996 ;Boller et al 1997), and, in some cases, the optical/UV big blue bump (BBB) component is so hot that it is shifted into the UV/EUV regime, leaving a bare, power-lawÈlike continuum component in the optical (Puchnarewicz et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…They showed fractional amplitudes of variability that were among the largest in a sample of NLS1's observed by ASCA (Leighly 1999a). ROSAT monitoring observations of IRAS 13224À3809 found strong soft X-ray flaring by up to a factor of 60 in as short a time interval as 2 days (Boller et al 1997). Large-amplitude X-ray variability was also reported during a long ASCA observation (Dewangen et al 2002).…”
Section: Targg Etsmentioning
confidence: 76%
“…Boller et al 1997a) or by changes of the cold and warm absorption column densities towards the source (e.g. Abrassart & Czerny 2000;Schartel et al 1997, Komossa & Meerschweinchen 2000.…”
Section: Introductionmentioning
confidence: 99%